1997
DOI: 10.1515/znb-1997-0206
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Structure, Vibrational Spectra and Thermal Analysis of Bis(saccharinato)bis(pyridine)zinc(II)

Abstract: The crystal structure of [Zn(sac)2(py)2] has been de termined by single-crystal X-ray diffractometry. It crystallizes in the monoclinic space group C2/c with Z = 4. We propose and discuss an assignment of its IR and Raman spectra, compatible with the structural characteristics. Its thermal behavior was investigated by means of TG and DTA methods. Some comparisons with related compounds are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 9 publications
6
25
0
Order By: Relevance
“…The mode known as amide II was identified as somewhat less intense band at 1580 cm -1 . The ligand bands located at 624 and 411 cm -1 and related to deformational modes of the pyridine ring [12] are displaced to higher frequencies (679 and 450 cm -1 , respectively) after coordination, showing a behavior similar to that observed for simple pyridine complexes [22]. This frequency analysis surely indicated that the coordination of nicotinamide to Fe(II) takes place via the pyridine ring nitrogen.…”
Section: Infrared Spectra and Spectra-structure Correlationssupporting
confidence: 59%
“…The mode known as amide II was identified as somewhat less intense band at 1580 cm -1 . The ligand bands located at 624 and 411 cm -1 and related to deformational modes of the pyridine ring [12] are displaced to higher frequencies (679 and 450 cm -1 , respectively) after coordination, showing a behavior similar to that observed for simple pyridine complexes [22]. This frequency analysis surely indicated that the coordination of nicotinamide to Fe(II) takes place via the pyridine ring nitrogen.…”
Section: Infrared Spectra and Spectra-structure Correlationssupporting
confidence: 59%
“…± The bending vibrations of the water molecules are probably superimposed with the bands found in the 1670±1571 cm ±1 region. ± The characteristic stretching vibrations of the SO 2 groups are found in the usual ranges, and the bands at 1365 and 949 cm ±1 have been assigned to the symmetric and antisymmetric stretching modes of the CNS unit of the saccharinate anion, as proposed in previous cases [8,9]. ± A number of very strong and characteristic bands, related to ring vibrations of the 1,10-phenanthroline ligand can be observed in the medium spectral range, between 1400±1600 cm ±1 [25,26].…”
Section: Infrared Spectrummentioning
confidence: 60%
“…Structural parameters for the ligand species are similar to those found, respectively, in free 1,10-phenanthroline [16] and in other saccharinate complexes (cf. for example [1,2,4,8,9, 17±21]).…”
Section: Crystal Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The assignment of some of the most characteristic bands of these molecules was performed with the aid of standard references [14,15]. In Table 3 we compare the most characteristic IR bands of the adducts, the diamines and the saccharinate in its sodium salt [16].…”
Section: Infrared Spectramentioning
confidence: 99%